O papel da gestão no cotidiano escolar na perspectiva inclusiva - SILVA, Waléria Almeida (2019)
The objective of this research is to contribute to a reflection on the role of school management in the process of inclusive education, not only of students with disabilities, but of all, regardless of race, religious issues, gender and ideologies. Thus, the main objective is to analyze the role of school management in an inclusive perspective in EEEFM Francisco Xavier in the municipality of Abaetetuba-PA. The methodology is based on qualitative research, having as steps to reach such objective was the bibliographic study and documentary analysis. Firstly, consultations were carried out on articles, periodicals and books, among which we highlight Mantoan (2003), Oliveira (2005), Aranha (2000), as well as some documents and declarations that regulate issues related to inclusive education. Regarding school management, the study was based on Luck (2001), Sousa (2002), Navarro (2004), Pacheco (2006), among others. The interviews, in loco, were carried out with six professionals (director, two vice principals and three pedagogical coordinators), where it was possible to arrive at some analyzes. The results showed that in view of the inclusion of all students, it is incumbent on the regular schools to develop a new school culture based on human rights, in particular, the right of all students to benefit from quality education. In this context, the role of the school manager will be to promote the transformation in the organizational forms of the school, eliminating the barriers that may impede the students' schooling process, involving in this process the whole school community, aiming at the construction of inclusive practices, shared mode.